Quick finite elements for electromagnetic waves - Pelosi, Giuseppe (Artech House electromagnetic analysis series., 2009)
The classic 1998 Artech House book, Quick Finite Elements for Electromagnetic Waves, has now been revised and expanded to bring you up-to-date with the latest developments in the Field. You find brand new discussions on finite elements in 3D, 3D resonant cavities, and 3D waveguide devices. Moreover, the second edition supplies you with MATLAB code, making this resource easier to comprehend and use for your projects in the field. This practical book and accompanying software enables you to quickly and easily work out challenging microwave engineering and high-frequency electromagnetic problems using the finite element method (FEM). Using clear, concise text and dozens of real-world application examples, the book provides a detailed description of FEM implementation, while the software provides the code and tools needed to solve the three major types of EM problems: guided propagation, scattering, and radiation. With this unique book and software set in hand, you can compute the dispersion diagram of arbitrarily shaped inhomogeneous isotropic lossless or lossy guiding structures, analyze E- and H-plane waveguide discontinuities and devices, and understand the reflection from and transmission through simple 2D and 3D inhomogeneous periodic structures. CD-ROM Included! Easy-to-use finite element software contains ready-made MATLAB and FORTRAN source code that you can use immediately to solve a wide range of microwave and EM problems. The package is fully compatible with Internet "freeware, " so you can perform advanced engineering functions without having to purchase expensive pre- and post-processing tools.